ODP.NET developer's guide : Oracle Database 10g development with Visual Studio 2005 and the Oracle data provider for .NET : a practical guide for developers working with the Oracle data provider for .NET and the Oracle developer tools for Visual Studio 2005 /: Oracle Database 10g development with Visual Studio 2005 and the Oracle data provider for .NET : a practical guide for developers working with the Oracle data provider for .NET and the Oracle developer tools for Visual Studio 2005. (2007) - Unknown
No abstract available